The Romantics of 1909: Arthur Symons, Pierre Lasserre and T. E. Hulme - Bénédicte COSTE (E-REA)
Arthur Symons’s The Romantic Movement in English Poetry (1909) has elicited scant discussion. Part dictionary of British authors born before 1800, part series of portraits of canonical Romantic poets, The Romantic Movement remains perplexing with its unclear purpose and ungainly format. This article argues that Symons’s monograph should be approached in the turn of the century debate on the definition and value of British Romanticism. As opposed to T. E. Hulme’s ‘Romanticism and Classicism’ (1912?), itself indebted to Pierre Lasserre’s Le Romantisme français. Essai sur la révolution dans les sentiments et dans les idées au XIXe siècle (1907), Symons’s study appears as a defence of the romantic aesthetics and fin the siècle cosmopolitanism against Lasserre’s and Hulme’s emphases on nationalism and Classicism.